Pengaruh Kecerdasan Menghadapi Hambatan dan Kecerdasan Emosional Terhadap Prestasi Belajar Ekonomi Siswa - Luluk Miratul Umah; Mintasih Indriayu; Aniek Hindrayani (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to analyze the influence of adversity quotient and emotional intelligence in influencing economic achievement of high school students in Madiun City. This research is a quantitative descriptive research. The research subjects studied were high school students in Madiun City who received economics subjects totaling 302 respondents. Data collection technique using purposive random sampling technique. Research data was taken using a questionnaire which was carried out offline by visiting schools. Data analysis technique using multiple linear regression analysis. The research results obtained are as follows. First, adversity quotient has a positive and significant effect on students' economic achievement. Second, emotional intelligence has a positive and significant effect on students' economic achievement. Third, adversity quotient and emotional intelligence has a positive and significant effect on students' economics learning achievement by 50.2%..